The Political Impact of King Abdullah II's Second Discussion Paper on the Development of Jordan's Democratic System: An Analytical Study of Political Parties (2013-2024) - Mefleh O., Hamdon, Hani; Hassan, Al Smadi, Essa Lafi; Hassan, Al-Jabali, Khaled (Journal of Ecohumanism, 2024)
Objectives: This study aimed to explore the political impact of His Majesty King Abdullah II's Second Discussion Paper on the development of the democratic system in Jordan, with a focus on the state of political parties during the period from 2013 to 2024. The Second Discussion Paper served as the primary concept (independent variable), and its influence on the evolution of political parties (dependent variable) within Jordan's democratic system was critically examined. The study was divided into two sections: the first addressed key concepts and the trajectory of democratic development in Jordan, while the second analyzed the impact of the Second Discussion Paper on political parties and their role in Jordanian political life. Methodology: A political analysis approach was employed to understand and interpret the influence of the Second Discussion Paper on political parties in Jordan, framed within the context of democratic theory. The analysis focused on the direct effects of the Discussion Paper on Jordan's political system, specifically examining the evolving role of political parties. Findings: The study found that the Second Discussion Paper significantly strengthened the role of political parties in Jordan by fostering national dialogue and supporting political pluralism. The Paper contributed to increased political participation by parties, enhanced their influence within the democratic process, and encouraged the development and reshaping of party roles within Jordan's political system. Conclusion: The study concluded that there is a strong correlation between the Second Discussion Paper and the development of Jordan's democratic system. The Paper contributed to empowering political parties, increasing their impact on political life, and reflecting the political leadership's commitment to ongoing democratic reforms.